W. J. Eccles: The Young Historian, 1951-63. - Miquelon, Dale (Journal of Canadian Studies)
W. J. Eccles's "Frontenac: The Courtier Governor" (1959) and his article "The History of New France According to Francis Parkman" (1961) established his reputation as a fearsome iconoclast. The myth of the heroic governor and the reputation of his nineteenth-century champion did not survive intact. Less dramatic but equally important was Eccles's exposition of French policy for the development of Canada in the seventeenth century, which he labelled Jean-Baptiste Colbert's "compact colony policy," a policy of limiting Canada's geographical extent Eccles made this idea, long-buried in his Master of Arts thesis (1951), the theme of his book "Canada under Louis XIV" (1964) in the Canadian Centenary Series. The division between volumes 3 and 4 reflects Eccles's belief, that from 1701 a new policy of continental imperialism replaced Colbert's old policy. Letters between Eccles and his editors, W. L. Morton and D. G. Creighton, reveal his struggle to include sections on economic and social history in a series decidedly narrative in structure. Canadian history writing was at a crossroads. Eccles was largely responsible for the rebirth of New France history in English. His influence was also felt among French-language historians, engaged in their own struggle to release history from a nineteenth-century embrace.